ANALISIS BIMBINGAN KONSELING ISLAM PADA PERSEPSI REMAJA TERHADAP PERILAKU HOMOSEKSUAL DI KABUPATEN KERINCI-JAMBI - Yulia Annisa (Universitas Islam Negeri Imam Bonjol Padang, 2020)
ABSTRACTIdeally, adolescents who have an Islamic education background are able to behave properly everyday. But in fact some of them have a tendency to deviant behavior, one of them homosexual behavior. This is caused by many factors, one of which is the factor of technological development that is so rapid that it brings negative values to the lives of adolescents. This research uses descriptive quantitative method. The population in this study were adolescents in the village of Kemantan Agung, Kerinci Regency aged 15 to 21 years totaling 102 people. To determine the sample size in this study using the Slovin formula, amounting to 81 people. Data collection techniques and tools in this study used a questionnaire in the form of a questionnaire. The results showed that; (1) in the aspect of understanding, 79% of adolescents have a level of understanding that is categorized as neutral (moderate), in other words the average teenager has enough understanding and enough understanding of knowledge about homosexual behavior; (2) in the assessment aspect, 75.3% of adolescents rated homosexual behavior as quite negative; (3) in the aspect of attitude of many adolescents or 56.8% of adolescents who are negative and refuse homosexual behavior occurs in their environment. Analysis of counseling techniques in an effort to improve understanding, assessment, and attitudes of adolescents towards homosexual behavior can be done with the KSKK counseling approach, individual counseling models and CBT counseling models.